Show that if mass = 0, then E=pc and u=c.
E^2 = (pc)^2 + (mc^2)^2
B = u/c = pc/E
The Attempt at a Solution
I understand that if m=0, then E^2=(pc)^2 => E=pc.
But isn't p = Ymu? then:
E^2 = (Ymuc)^2 + (mc^2)^2
Plugging in m=0 sets E=0...
It seems strange to me that we can remove (mc^2)^2 from the equation due to m=0, but we can leave (Ymuc)^2 in.
I'm thinking that this definition of p is not the same as Ymu?
EDIT: wait... Y would equal infinity. Which multiplied with 0 makes ??? I'm just plain confused now.